Method for preparing collagen-based nanofiber membrane using leather scraps as raw materials

Collagen is extracted through leather chip hydrolysis and electrospinning is used to prepare collagen-based nanofiber membranes, which solves the problems of high raw materials prices and low production efficiency in the existing technology, and realizes efficient and environmentally friendly collagen-based nanofiber membrane preparation. in a variety of application fields.

CN115012119BActive Publication Date: 2025-01-07BEIJING UNIV OF CHEM TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110240240.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-03-04
Publication Date
2025-01-07
Estimated Expiration
2041-03-04

AI Technical Summary

Technical Problem

In the prior art, the raw materials for preparing collagen-based nanofiber membranes are expensive and have low production efficiency, making it difficult to achieve large-scale production, and the collagen extraction process is complex and unfriendly to the environment.

Method used

Leather chips are used as raw materials to extract collagen by hydrolysis by alkali urea method, and collagen-based nanofiber membranes are prepared in combination with electrospinning, which improves leather chip utilization and simplifies the process flow.

Benefits of technology

It realizes efficient preparation of collagen-based nanofiber membranes, with leather chip utilization rate reaching more than 80%, reducing production costs, and providing a green and environmentally friendly high-value-added leather waste path suitable for biomaterials and flexible electronics. Skin and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115012119B_ABST
    Figure CN115012119B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a collagen-based nanofiber membrane using leather scraps as raw materials, comprising the following steps: crushing, grinding, and sieving leather scraps to obtain dry leather scraps crude fibers; first preparing an alkaline urea solution, then mixing the leather scraps crude fibers with the alkaline urea solution, stirring and hydrolyzing to obtain a clarified leather scraps hydrolyzate; centrifuging and dialyzing the leather scraps hydrolyzate to purify it, to obtain a leather scraps hydrolyzate purified liquid; adding a water-soluble organic polymer to water, stirring and dissolving it under heating conditions, to obtain an organic polymer solution; blending the leather scraps hydrolyzate purified liquid with the organic polymer solution, stirring, ultrasonically dispersing, standing to remove foam, to obtain a uniformly mixed spinning solution; using an electrostatic spinning device, the spinning solution is made into a collagen-based nanofiber membrane. The method for preparing the collagen-based composite nanofiber membrane according to the present invention is simple and efficient, with a leather scraps utilization rate of more than 80%, and the product has broad application prospects in the fields of biomaterials, nano energy, and flexible electronic skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of leather recycling, and in particular relates to a method for preparing a collagen-based nanofiber membrane using leather scraps as raw materials. Background Art

[0002] As a traditional industry in my country, the leather industry faces two major problems: waste of resources and environmental pollution. Animal skins are the basic raw materials of the leather industry, but usually only about 20-50% will be transformed into leather, and the rest will be treated in the form of scraps and scraps, such as incineration, landfill, etc., which not only causes waste of raw materials, but also produces solid waste pollution, increasing the difficulty of environmental treatment; or produces low value-added products such as recycled leather. Among these leather wastes, 80% are skin collagen fibers, which are based on collagen molecules with a triple helix structure as the basic unit. Collagen is the main component of the extracellular matrix and has the advantages of low immunogenicity, biodegradability, high tensile strength, low ductility, etc. It is a good biomaterial. In order to find a green, environmentally friendly and high value-added utilization path for leather industry waste, the extraction and utilization of skin collagen fibers in leather scraps has become a current research hotspot. The extracted collagen can be applied in different forms to food, medical, leather, papermaking, degradable materials, beauty cosmetics, feed, fertilizer and other fields after different processing methods.

[0003] The main methods for extracting collagen from leather scraps by hydrolysis include acid method, alkaline method and enzymatic method. Acid hydrolysis has little damage to collagen, but the cycle is long and the hydrolysis efficiency is low; the ordinary alkaline hydrolysis cycle is short, but the degree of damage to collagen is greater; the enzymatic hydrolysis process is complicated and the cost is high.

[0004] At present, the method of preparing collagen-based nanofiber membranes has been reported. Chinese patent document CN 107693835A discloses a polyvinyl alcohol / collagen / quaternized chitosan electrospinning composite fiber membrane and its preparation method. The collagen used comes from homemade marine fish skin collagen; Chinese patent document CN 105926076 A discloses a method for preparing collagen / polyvinyl alcohol / polylactic acid composite fibers, and the spinnability of the mixed solution is achieved by adjusting the proportion of each raw material. The raw collagen used in the above technology is purified through complex processes, the price is high and the production efficiency is low. If large-scale production is to be achieved, it is necessary to find cheaper and more extensive collagen raw materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing collagen-based nanofiber membranes using leather scraps as raw materials; the present invention uses leather scraps hydrolyzate with collagen as the main component as raw material and prepares collagen-based composite nanofiber membranes by electrospinning. The collagen-based nanofiber membranes prepared by the present invention using leather scraps as raw materials have broad application prospects in the fields of biomaterials, nano energy, flexible electronic skin, etc., and also provide a green, environmentally friendly, and high value-added utilization path for leather industry waste. The method of the present invention is simple and quick, and the utilization rate of leather scraps is more than 80%.

[0006] The term "leather scraps" in the present invention refers to the tanning scraps from tanning leather after aldehyde tanning or other methods of tanning.

[0007] In order to solve the above technical problems, the invention adopts the following technical solutions:

[0008] A method for preparing a collagen-based nanofiber membrane using leather scraps as raw materials comprises the following steps:

[0009] 1) crushing, grinding and sieving leather scraps to obtain dry leather scrap crude fibers;

[0010] 2) first preparing an alkaline urea solution, then mixing the leather scraps crude fiber with the alkaline urea solution, stirring and hydrolyzing, and obtaining a clarified leather scraps hydrolyzate;

[0011] 3) purifying the leather scraps hydrolyzate by centrifugation and dialysis to obtain a leather scraps hydrolyzate purified liquid;

[0012] 4) adding a water-soluble organic polymer to water, stirring and dissolving the water under heating conditions to obtain an organic polymer solution;

[0013] 5) blending the leather scraps hydrolysis purification liquid with the organic polymer solution, stirring evenly, ultrasonically dispersing, standing to remove foam, and obtaining a uniformly mixed spinning solution;

[0014] 6) Using an electrospinning device and setting appropriate process parameters, the spinning solution is made into a collagen-based nanofiber membrane.

[0015] As a further improvement of the technical solution, in step 1), the size of the leather scraps coarse fibers is 20-30 mesh, 30-40 mesh or 40-50 mesh.

[0016] Preferably, in step 2), the alkali in the alkaline urea solution is selected from one or more of NaOH, KOH and LiOH.

[0017] Preferably, in step 2), the alkaline urea solution has an alkali content of 5 to 12 wt % and a urea content of 1 to 20 wt %.

[0018] Preferably, in step 2), the weight ratio of the leather scrap crude fiber to the alkaline urea solution is 1:15-1:30, the stirring time is 3-6 hours, and the hydrolysis temperature is 25-45°C.

[0019] As a further improvement of the technical solution: in step 3), the centrifugal dialysis purification of the leather scraps hydrolyzate comprises the following specific steps:

[0020] 31) adding an acid solution to the collagen hydrolyzate obtained in step 2) to adjust the pH to 6.5-7.5, and letting it stand to remove foam;

[0021] 32) centrifuging the collagen hydrolyzate obtained in step 31) to separate the insoluble precipitate in the lower layer and retaining the supernatant;

[0022] 33) The supernatant is placed in a dialysis bag and dialyzed in deionized water to remove small molecule impurities (such as urea and sodium chloride) to obtain a dialysate;

[0023] 34) The dialyzate is subjected to rotary evaporation to remove part of the water to obtain a leather shavings hydrolyzate purified liquid whose main component is collagen.

[0024] Preferably, in step 31), the acid is one or more of glacial acetic acid, dilute hydrochloric acid, and dilute sulfuric acid.

[0025] Preferably, in step 32), the centrifugal speed is 10000-12000 rpm, and the centrifugal time is 15-25 minutes.

[0026] Preferably, in step 33), the molecular weight cutoff of the dialysis bag is 1000-2000, and the dialysis time is 3-5 days.

[0027] Preferably, in step 34), the rotary evaporation temperature is 40-60° C., the rotary evaporation time is 3-6 hours, and the mass fraction of collagen after rotary evaporation is 30%-60%.

[0028] As a further improvement of the technical solution, in step 4), the water-soluble organic polymer is selected from one or more of polyethylene oxide, polyvinyl pyrrolidone, and polyacrylic acid. These substances are both water-soluble and have a certain viscosity, and are used to increase the viscosity of the hydrolyzate.

[0029] As a further improvement of the technical solution, in step 5), the mass ratio of the leather shavings hydrolysis purification liquid to the organic polymer solution is 1:1-2:1, the stirring time is 1-3h, the ultrasonic dispersion time is 20-40min, and the standing time is 1-2h.

[0030] Preferably, in step 5), the spinning solution is further doped with 1-10% by mass of a nano-conductive material; more preferably, the nano-conductive material is selected from one or more of silver nanoparticles, copper nanoparticles, silver nanowires, and carbon nanotubes.

[0031] As a further improvement of the technical solution, in step 6), the process parameters include: voltage 18-25 kV, receiving distance 15-20 cm, spinning solution feed rate 0.005-0.02 mL / min.

[0032] Preferably, in step 6), the spinning environment conditions are a temperature of 20±10° C. and a humidity of 30±20%.

[0033] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0034] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. Collagen-based composite materials are prepared with leather collagen fibers in leather waste shavings as the basic raw materials. The raw materials are widely available, low in price and low in cost. At the same time, the utilization rate of leather shavings reaches more than 80%, which is an environmentally friendly and high-value-added leather waste utilization path.

[0037] 2. The alkali urea method is used to hydrolyze leather scraps. The steps are simple, the hydrolysis time is short, and the leather scraps utilization rate is high. The addition of urea can stabilize the hydrophobic part of the collagen molecule, reduce the direct interaction with polar solvents, and prevent excessive hydrolysis of the skin collagen fibers. The final hydrolyzate can retain the secondary structure of collagen.

[0038] 3. Electrospinning is used to efficiently prepare nanofibers. The spinnability of leather shavings hydrolyzate is achieved by optimizing spinning conditions such as changing the material ratio and adding nano-conductive materials. Composite nanofibers with uniform morphology are prepared, which can be applied to the fields of biomaterials, flexible electronic skin, nano-energy, etc. The collagen-based nanofiber membrane prepared by the present invention can be used to prepare friction nanogenerators to convert mechanical energy into electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0040] Figure 1 This is a scanning electron microscope image of the components of the dandruff hydrolyzate of the present invention;

[0041] Figure 2 is a scanning electron microscope image of the product of Example 1 of the present invention;

[0042] Figure 3 is a scanning electron microscope image of the product of Example 2 of the present invention;

[0043] Figure 4 is a scanning electron microscope image of the product of Example 3 of the present invention;

[0044] Figure 5 is the stress-strain curve of the product of Example 1 of the present invention;

[0045] Figure 6 The product of Example 1 of the present invention is assembled into a triboelectric nanogenerator voltage output;

[0046] Figure 7 The product of Example 1 of the present invention is assembled into a friction nanogenerator and the voltage output is tested 1000 times in a cycle;

[0047] Figure 8 is the stress-strain curve of the product of Example 2 of the present invention;

[0048] Fig. 9 The product of Example 2 of the present invention is assembled into a triboelectric nanogenerator voltage output;

[0049] Fig.10 is the stress-strain curve of the product of Example 3 of the present invention;

[0050] Fig.11 The product of Example 3 of the present invention is assembled into a triboelectric nanogenerator voltage output;

[0051] Fig.12 is a scanning electron microscope image of the product of Comparative Example 1 of the present invention; DETAILED DESCRIPTION

[0052] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0053] As one aspect of the present invention, a method for preparing a collagen-based nanofiber membrane using leather scraps as raw materials comprises the following steps:

[0054] 1) crushing, grinding and sieving leather scraps to obtain dry leather scrap crude fibers;

[0055] 2) first preparing an alkaline urea solution, then mixing the leather scraps crude fiber with the alkaline urea solution, stirring and hydrolyzing, and obtaining a clarified leather scraps hydrolyzate;

[0056] 3) purifying the leather scraps hydrolyzate by centrifugation and dialysis to obtain a leather scraps hydrolyzate purified liquid;

[0057] 4) adding a water-soluble organic polymer to water, stirring and dissolving the water under heating conditions to obtain an organic polymer solution;

[0058] 5) blending the leather scraps hydrolysis purification liquid with the organic polymer solution, stirring evenly, ultrasonically dispersing, standing to remove foam, and obtaining a uniformly mixed spinning solution;

[0059] 6) Using an electrospinning device and setting appropriate process parameters, the spinning solution is made into a collagen-based nanofiber membrane.

[0060] It should be noted that the leather shavings hydrolyzate in the technical solution of the present invention cannot be spun directly. First, water as a solvent has a higher dielectric constant, which leads to the attenuation of the electrostatic repulsion between the surface charges of the jet. To achieve a stable jet, a larger external voltage or external nano-conductive material is required; second, the low viscosity of the solution is not conducive to the stretching of the jet by the electric field force to form continuous fibers, so a polymer with a certain viscosity needs to be added to aid spinning.

[0061] According to some embodiments of the present invention, in step 1), the size of the leather scraps coarse fibers is 20-30 mesh, 30-40 mesh or 40-50 mesh.

[0062] According to some embodiments of the present invention, in step 2), the alkali in the alkaline urea solution is selected from one or more of NaOH, KOH, and LiOH.

[0063] According to certain embodiments of the present invention, in step 2), the alkaline urea solution has an alkali content of 5 to 12 wt % and a urea content of 1 to 20 wt %.

[0064] According to certain embodiments of the present invention, in step 2), the weight ratio of the leather scrap crude fiber to the alkaline urea solution is 1:15-1:30, the stirring time is 3-6 hours, and the hydrolysis temperature is 25-45°C.

[0065] According to certain embodiments of the present invention, in step 3), the centrifugal dialysis purification of the leather scraps hydrolyzate comprises the following specific steps:

[0066] 31) adding an acid solution to the collagen hydrolyzate obtained in step 2) to adjust the pH to 6.5-7.5, and letting it stand to remove foam;

[0067] 32) centrifuging the collagen hydrolyzate obtained in step 31) to separate the insoluble precipitate in the lower layer and retaining the supernatant;

[0068] 33) The supernatant is placed in a dialysis bag and dialyzed in deionized water to remove small molecule impurities (such as urea and sodium chloride) to obtain a dialysate;

[0069] 34) The dialyzate is subjected to rotary evaporation to remove part of the water to obtain a leather shavings hydrolyzate purified liquid whose main component is collagen.

[0070] According to certain preferred embodiments of the present invention, in step 31), the acid is one or more of glacial acetic acid, dilute hydrochloric acid, and dilute sulfuric acid.

[0071] According to certain preferred embodiments of the present invention, in step 32), the centrifugal speed is 10000-12000 rpm, and the centrifugal time is 15-25 minutes.

[0072] According to certain preferred embodiments of the present invention, in step 33), the molecular weight cutoff of the dialysis bag is 1000-2000, and the dialysis time is 3-5 days.

[0073] According to certain preferred embodiments of the present invention, in step 34), the rotary evaporation temperature is 40-60° C., the rotary evaporation time is 3-6 hours, and the mass fraction of collagen after rotary evaporation is 30%-60%.

[0074] According to some embodiments of the present invention, in step 4), the water-soluble organic polymer is selected from one or more of polyethylene oxide, polyvinyl pyrrolidone, and polyacrylic acid. These substances are both water-soluble and have a certain viscosity, and are used to increase the viscosity of the hydrolyzate.

[0075] According to certain embodiments of the present invention, in step 5), the mass ratio of the leather shavings hydrolysis purification liquid to the organic polymer solution is 1:1-2:1, the stirring time is 1-3h, the ultrasonic dispersion time is 20-40min, and the standing time is 1-2h.

[0076] According to some embodiments of the present invention, in step 5), the spinning solution is further doped with a nano-conductive material with a mass fraction of 1-10%; more preferably, the nano-conductive material is selected from one or more of silver nanoparticles, copper nanoparticles, silver nanowires, and carbon nanotubes.

[0077] According to certain embodiments of the present invention, in step 6), the process parameters include: voltage 18-25 kV, receiving distance 15-20 cm, spinning solution feed rate 0.005-0.02 mL / min.

[0078] According to certain embodiments of the present invention, in step 6), the spinning environment conditions are a temperature of 20±10° C. and a humidity of 30±20%.

[0079] Example 1

[0080] A method for preparing a collagen-based nanofiber membrane using leather scraps as raw materials comprises the following steps:

[0081] 1) crushing the raw leather scraps, grinding them thoroughly, and sieving them to obtain 30-40 mesh dry leather scraps crude fibers;

[0082] 2) Weigh 7 g of sodium hydroxide, 12 g of urea, and 81 g of water respectively, mix them in a beaker, and stir evenly to prepare an alkaline urea solution;

[0083] 3) Weigh 4 g of treated leather scraps crude fiber and mix with 80 ml of alkaline urea solution, and stir at 35° C. for 4 hours to obtain a clear collagen hydrolyzate;

[0084] 4) Measure 9 ml of glacial acetic acid solution to adjust the pH of the hydrolyzate. After standing for half an hour to remove bubbles, centrifuge at 12,000 rpm for 15 minutes. Pour the supernatant into a dialysis bag with a molecular weight cutoff of 1,000 and dialyze with deionized water for 72 hours to remove small molecular impurities such as urea and sodium chloride. Vacuum the dialyzate at 45°C for 4 hours to obtain about 10 g of collagen-containing hydrolyzate;

[0085] 5) Weigh 10 g of polyvinyl alcohol (1788 type) and add it to 40 g of deionized water, stir and dissolve at 80° C. for 4 hours to prepare a 20% mass concentration PVA solution;

[0086] 6) Weigh 4 g of the hydrolyzate in step 4) and 4 g of the prepared 20% PVA solution, mix and stir for 4 hours, ultrasonicate for 20 minutes, and stand for half an hour to degas to obtain a uniformly mixed spinning solution;

[0087] 7) Setting spinning conditions: process parameters: voltage 25 kV, receiving distance 20 cm, feed rate 0.01 mL / min. Environmental conditions are temperature 20° C., humidity 40%, and spinning for 10 hours to obtain collagen / polyvinyl alcohol composite nanofiber film.

[0088] Application of the nanofiber film prepared in Example 1: Assembling a triboelectric nanogenerator to test the electrical output performance: Cut out a 3×3 cm 2 The fiber membrane of different sizes is attached to the aluminum foil, and the aluminum foil surface is bonded with a copper wire with a conductive copper tape as the triboelectric positive electrode material. In the same way, the polyvinylidene fluoride fiber membrane made by laboratory electrospinning method is used as the triboelectric negative electrode material. The continuous contact and separation experiment is carried out through the motor test platform while detecting the voltage output.

[0089] After testing, the nanofiber film obtained in this embodiment has a thickness of 0.16 mm, an elastic modulus of 11.95 MPa, a tensile strength of 2.76 MPa, and a stress-strain curve as shown in Figure 5 As shown, it has good flexibility and mechanical properties. Figure 6-7As shown, the open circuit voltage of the prepared friction nanogenerator is 190V, and the output performance remains unchanged after 1000 cycle tests, and it has good wear resistance.

[0090] Example 2

[0091] The method for preparing collagen / polyvinyl alcohol / silver nanowire composite nanofibers using leather shavings hydrolyzate as raw material comprises the following steps:

[0092] 1) The raw leather scraps are crushed and fully ground, and sieved to obtain 30-40 mesh dry leather scrap crude fibers.

[0093] 2) Weigh 5 g of sodium hydroxide, 15 g of urea and 20 g of water respectively, mix them in a beaker, and stir them evenly to prepare an alkaline urea solution.

[0094] 3) Weigh 4 g of treated leather crude fiber and mix with 60 ml of alkaline urea solution, and stir at 40°C for 3 hours.

[0095] 4) Take an appropriate amount of dilute sulfuric acid solution to adjust the pH of the hydrolyzate to about 7. Centrifuge at 12,000 rpm for 15 minutes, pour the supernatant into a dialysis bag with a molecular weight cutoff of 1,500 and dialyze with deionized water for 60 hours to remove small molecular impurities such as urea and sodium chloride. Vacuum the dialyzate at 50°C for 3 hours to obtain about 8 g of collagen-containing hydrolyzate.

[0096] 5) Weigh 10 g of polyvinyl alcohol (1788 type) and add it to 40 g of deionized water, stir and dissolve it at 80° C. for 4 hours to prepare a PVA solution with a mass concentration of 20%.

[0097] 6) Weigh 4 g of the hydrolyzate prepared in step 4), add 0.8 g of self-made silver nanowires with a solid content of 80%, a diameter of 90 nm, and a length of 10-20 μm, and perform ultrasonic treatment for 20 minutes to achieve uniform dispersion.

[0098] 7) Weigh 4 g of the prepared 20% PVA solution and add it to the mixed dispersion in step 6), stir for 4 hours, ultrasonicate for 30 minutes, and stand for half an hour to degas to obtain a uniformly mixed spinning solution.

[0099] 8) Setting spinning conditions: process parameters: voltage 20 kV, receiving distance 20 cm, feed rate 0.02 mL / min. Environmental conditions: temperature 15° C., humidity 10%-20%, spinning for 6 hours of collagen / polyvinyl alcohol / silver nanowire composite nanofiber film.

[0100] Application of the prepared nanofiber film in Example 2: Assembling a friction nanogenerator to test the electrical output performance: Cut out a 2×2 cm 2The fiber membrane of different sizes is attached to the aluminum foil, and the aluminum foil surface is bonded with a copper wire with a conductive copper tape as the triboelectric positive electrode material. In the same way, the polyvinylidene fluoride fiber membrane made by laboratory electrospinning method is used as the triboelectric negative electrode material. The continuous contact and separation experiment is carried out through the motor test platform while detecting the voltage output.

[0101] After testing, the nanofiber film obtained in this embodiment has a thickness of 0.12 mm, an elastic modulus of 16.78 MPa, a tensile strength of 2.41 MPa, and a stress-strain curve as shown in FIG. Figure 8 As shown in Figure 1, it has good mechanical properties. Fig. 9 As shown, the open circuit voltage of the prepared friction nanogenerator is 118V.

[0102] Example 3

[0103] The method for preparing collagen / polyvinyl alcohol / carbon nanotube composite nanofibers using leather shavings hydrolyzate as raw material comprises the following steps:

[0104] 1) The raw leather scraps are crushed and fully ground, and sieved to obtain 20-30 mesh dry leather scrap crude fibers.

[0105] 2) Weigh 8 g of potassium hydroxide, 12 g of urea and 20 g of water respectively, mix them in a beaker, and stir them evenly to prepare an alkaline urea solution.

[0106] 3) Weigh 4 g of treated leather crude fiber and mix with 80 ml of alkaline urea solution, and stir at 35°C for 4 hours.

[0107] 4) Take an appropriate amount of phosphoric acid solution to adjust the pH of the hydrolyzate to about 7. Centrifuge at 10,000 rpm for 25 minutes, pour the supernatant into a dialysis bag with a molecular weight cutoff of 1,000 and dialyze with deionized water for 72 hours. Vacuum evaporate the dialyzate at 45°C for 4.5 hours to obtain about 10 g of collagen-containing hydrolyzate.

[0108] 5) Weigh 10 g of polyvinyl alcohol (1788 type) and add it to 40 g of deionized water, stir and dissolve it at 80° C. for 4 hours to prepare a PVA solution with a mass concentration of 20%.

[0109] 6) Weigh 4 g of the hydrolyzate obtained in step 4), add 0.16 g of carboxylated multi-walled carbon nanotubes, mix and stir for 1 h, and ultrasonicate for 30 min to ensure uniform dispersion.

[0110] 7) Weigh 4 g of the prepared 20% PVA solution and add it to the mixed dispersion in step 6), stir for 4 hours, ultrasonicate for 30 minutes, and stand for half an hour to degas to obtain a uniformly mixed spinning solution.

[0111] 8) Setting spinning conditions: process parameters: voltage 22 kV, receiving distance 18 cm, feed rate 0.01 mL / min. Environmental conditions: temperature 20° C., humidity 15%-25%, spinning for 5 hours to obtain collagen / polyvinyl alcohol / carbon nanotube composite nanofiber film.

[0112] Application of the prepared nanofiber film in Example 3: Assembling a triboelectric nanogenerator to test the electrical output performance: Cut out a 2×2 cm 2 The fiber membrane of different sizes is attached to the aluminum foil, and the aluminum foil surface is bonded with a copper wire with a conductive copper tape as the triboelectric positive electrode material. In the same way, the polyvinylidene fluoride fiber membrane made by laboratory electrospinning method is used as the triboelectric negative electrode material. The continuous contact and separation experiment is carried out through the motor test platform while detecting the voltage output.

[0113] After testing, the nanofiber film obtained in this embodiment has a thickness of 0.09 mm, an elastic modulus of 39.9 MPa, a tensile strength of 2.99 MPa, and a stress-strain curve as shown in FIG. Fig.10 As shown in Figure 1, it has good mechanical properties. Fig.11 As shown, the open circuit voltage of the prepared friction nanogenerator is 94V.

[0114] Comparative Example 1

[0115] Example 1 was repeated, except that the mass ratio of the purified hydrolyzed leather scraps solution to the organic polymer solution was 3:1. Step 6) was changed to: weigh 6 g of the hydrolyzed solution in step 4) and 2 g of the prepared 20% PVA solution. Other conditions and specific operation steps were completely consistent with Example 1.

[0116] The results show that the comparative example is unstable during the electrospinning process, and the obtained composite nanofiber film has different thicknesses, a rough surface, and a microscopic morphology. Fig.12 shown.

[0117] Comparative Example 2

[0118] Example 1 was repeated, except that the electrospinning voltage conditions were different. Step 7) The spinning voltage was set to 15 kV, and the other conditions and specific operation steps were completely consistent with those of Example 1.

[0119] The results show that a large amount of liquid dripping occurs during the electrospinning process in this comparative example, and continuous spinning to form a fiber membrane cannot be achieved.

[0120] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing collagen-based nanofiber membranes using leather scraps as raw materials, characterized in that: It consists of the following steps: 1) Crush, grind and sieve leather scraps to obtain dry leather scrap crude fibers; 2) First prepare an alkaline urea solution, then mix the leather scraps crude fiber with the alkaline urea solution, stir and hydrolyze to obtain a clear leather scraps hydrolyzate; 3) Purifying the leather shavings hydrolyzate by centrifugation and dialysis to obtain a leather shavings hydrolyzate purified liquid; 4) Adding water-soluble organic polymer to water, stirring and dissolving under heating conditions to obtain an organic polymer solution; 5) Blending the leather scraps hydrolysis purification liquid with the organic polymer solution, stirring evenly, ultrasonically dispersing, standing to remove foam, and obtaining a uniformly mixed spinning solution; 6) using an electrospinning device and setting appropriate process parameters to form a collagen-based nanofiber membrane from the spinning solution; In step 5), the mass ratio of the leather scraps hydrolysis purification liquid to the organic polymer solution is 1:1-2:1; In step 6), the process parameters include: voltage 18-25 kV, receiving distance 15-20 cm, spinning solution feed rate 0.005-0.02 mL / min.

2. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 1, characterized in that: In step 1), the size of the leather scraps coarse fibers is 20-30 mesh, 30-40 mesh or 40-50 mesh.

3. The method for preparing collagen-based nanofiber membrane using leather scraps as raw materials according to claim 1, characterized in that: In step 2), the alkali in the alkaline urea solution is selected from one or more of NaOH, KOH and LiOH.

4. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 1, characterized in that: In step 2), the alkaline urea solution has an alkali content of 5 to 12 wt % and a urea content of 1 to 20 wt %.

5. The method for preparing collagen-based nanofiber membrane using leather scraps as raw materials according to claim 1, characterized in that: In step 2), the weight ratio of the leather scraps crude fiber to the alkaline urea solution is 1:15-1:30, the stirring time is 3-6 hours, and the hydrolysis temperature is 25-45°C.

6. The method for preparing collagen-based nanofiber membrane using leather scraps as raw materials according to claim 1, characterized in that: In step 3), the leather scraps hydrolyzate is purified by centrifugal dialysis, comprising the following specific steps: 31) adding an acid solution to the collagen hydrolyzate obtained in step 2) to adjust the pH to 6.5-7.5, and letting it stand to remove the foam; 32) centrifuging the collagen hydrolyzate obtained in step 31) to separate the insoluble precipitate in the lower layer and retaining the supernatant; 33) The supernatant is placed in a dialysis bag and dialyzed in deionized water to remove small molecule impurities to obtain a dialysate; 34) The dialyzate is subjected to rotary evaporation to remove part of the water to obtain a leather shavings hydrolyzate purified liquid whose main component is collagen.

7. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 6, characterized in that: In step 31), the acid is one or more of glacial acetic acid, dilute hydrochloric acid, and dilute sulfuric acid.

8. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 6, characterized in that: In step 32), the centrifugal speed is 10000-12000 rpm, and the centrifugal time is 15-25 minutes.

9. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 6, characterized in that: In step 33), the molecular weight cutoff of the dialysis bag is 1000-2000, and the dialysis time is 3-5 days.

10. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 6, characterized in that: In step 34), the rotary evaporation temperature is 40-60° C., the rotary evaporation time is 3-6 hours, and the mass fraction of collagen after rotary evaporation is 30%-60%.

11. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 1, characterized in that: In step 4), the water-soluble organic polymer is selected from one or more of polyethylene oxide, polyvinyl pyrrolidone and polyacrylic acid.

12. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 1, characterized in that: In step 5), the stirring time is 1-3 hours, the ultrasonic dispersion time is 20-40 minutes, and the standing time is 1-2 hours.

13. The method for preparing collagen-based nanofiber membranes using leather scraps as raw materials according to claim 1, characterized in that: In step 5), the spinning solution is also doped with a nano-conductive material in a mass fraction of 1-10%.

14. The method for preparing collagen-based nanofiber membrane using leather scraps as raw materials according to claim 13, characterized in that: The nano-conductive material is selected from one or more of silver nanoparticles, copper nanoparticles, silver nanowires, and carbon nanotubes.

15. The method for preparing collagen-based nanofiber membrane using leather scraps as raw materials according to claim 1, characterized in that: In step 6), the spinning environment conditions are temperature 20±10° C. and humidity 30±20%.

Citation Information

Patent Citations

  • Collagen / polyvinyl alcohol / polylactic acid composite fiber

    CN105926076A

  • A polyvinyl alcohol / collagen / quaternized chitosan electrospun composite fiber film and a preparing method thereof

    CN107693835A

  • Preparation method of PEO-containing collagen-base nanofiber membrane

    CN105568559A

  • Method for preparing collagen-based composite degradable fiber from metal particle containing leather chips

    CN108396403A